Pleomorphism in the Antarctic flagellate Pyramimonas gelidicola (Prasinophyceae, Chlorophyta) - van den Hoff, John; Ferris, John M (Polar Research, 2009)
Species of the genus Pyramimonas (Prasinophyceae) are a common, widespread, but minor component of the Antarctic marine phytoplankton. They are often associated with the seasonal sea-ice environment. Pyramimonas gelidicola (McFadden, Moestrup & Wetherbee, 1982) was isolated from the water column of a saline Antarctic lake, and observations on the organism’s life history as it grew in unialgal cultures were made. The alga proved to be pleomorphic: capable of producing several morphologically distinct life stages. We recorded motile single-celled quadriflagellates that formed two statistically distinct size classes, a rare uniflagellate cell-type, and aggregations of quadriflagellate cells, multilobed forms and an encystment stage. Multilobed forms and cell aggregations, never before observed in an Antarctic Pyramimonas species, are presumed to be growth medium-induced morphotypes. Multilobed forms contained an equal number of nuclei and lobes, suggesting that they are the product of asexual reproduction. Some of the morphotypes we report here may never be observed under natural field conditions, but the potential for this alga to alternate between morphotypes is clearly demonstrated.
Keywords: Sørishavet; alger; fytoplankton; marin biologi

Comparison of the microalgal community within fast ice at two sites along the Ross Sea coast, Antarctica - Ryan, K.G.; Hegseth, E.N.; Martin, A.; Davy, S.K.; O'Toole, R.; Ralph, P.J.; McMinn, A.; Thorn, C.J. (Antarctic Science, 2006)
Diverse microbial communities survive within the sea ice matrix and are integral to the energy base of the Southern Ocean. Here we describe initial findings of a four season survey (between 1999–2004) of community structure and biomass of microalgae within the sea ice and in the underlying water column at Cape Evans and Cape Hallett, in the Ross Sea, Antarctica as part of the Latitudinal Gradient Project. At Cape Evans, bottom-ice chlorophyll a levels ranged from 4.4 to 173 mg Chl a m−2. Dominant species were Nitzschia stellata, N. lecointei, and Entomoneis kjellmanii, while the proportion of Berkeleya adeliensis increased steadily during spring. Despite being obtained later in the season, the Cape Hallett data show considerably lower standing stocks of chlorophyll ranging from 0.11 to 36.8 mg Chl a m−2. This difference was attributed to a strong current, which may have ablated much of the bottom ice biomass and provided biomass to the water below. This loss of algae from the bottom of the ice may explain why the ice community contributed only 2% of the standing stock in the total water column. Dominant species at Cape Hallett were Nitzschia stellata, Fragilariopsis curta and Cylindrotheca closterium. The low biomass at Cape Hallett and the prevalence of smaller-celled diatoms in the bottom ice community indicate that the ice here is more typical of pack ice than fast ice. Further data will allow us to quantify and model the extent to which ice-driven dynamics control the structure and function of the sea ice ecosystem and to assess its resilience to changing sea ice conditions.
Edition: 2006/11/14 Publisher: Cambridge University Press
Keywords: Rosshavet; Sørishavet; alger; biomasse; fytoplankton; marin biologi

Iron and mixing affect biological carbon uptake in SOIREE and EisenEx, two Southern Ocean iron fertilisation experiments - Bakker, Dorothee C.E.; Bozec, Yann; Nightingale, Philip D.; Goldson, Laura; Messias, Marie-José; de Baar, Hein J.W.; Liddicoat, Malcolm; Skjelvan, Ingunn; Strass, Volker; Watson, Andrew J. (Deep Sea Research Part I: Oceanographic Research Papers, 2005)
This study explores the changes in the surface water fugacity of carbon dioxide (fCO2) and biological carbon uptake in two Southern Ocean iron fertilisation experiments with different hydrographic regimes. The Southern Ocean Iron Release Experiment (SOIREE) experiment was carried out south of the Antarctic Polar Front (APF) at 61°S, 141°E in February 1999 in a stable hydrographic setting. The EisenEx experiment was conducted in a cyclonic eddy north of the APF at 48°S, 21°E in November 2000 and was characterised by a rapid succession of low to storm-force wind speeds and dynamic hydrographic conditions. The iron additions promoted algal blooms in both studies. They alleviated algal iron limitation during the 13-day SOIREE experiment and probably during the first 12 days of EisenEx. The fCO2 in surface water decreased at a constant rate of 3.8μatmday−1 from 4 to 5 days onwards in SOIREE. The fCO2 reduction was 35μatm after 13 days. The evolution of surface water fCO2 in the iron-enriched waters (or ‘patch’) displayed a saw tooth pattern in EisenEx, in response to algal carbon uptake in calm conditions and deep mixing and horizontal dispersion during storms. The maximum fCO2 reduction was 18–20μatm after 12 and 21 days with lower values in between. The iron-enriched waters in EisenEx absorbed four times more atmospheric CO2 than in SOIREE between 5 and 12 days, as a result of stronger winds. The total biological uptake of inorganic carbon across the patch was 1389ton C (±10%) in SOIREE and 1433ton C (±27%) in EisenEx after 12 days (1ton=106g). This similarity probably reflects the comparable size of the iron additions, as well as algal growth at a similar near-maximum growth rate in these regions. The findings imply that the different mixing regimes had less effect on the overall biological carbon uptake across the iron-enriched waters than suggested by the evolution of fCO2 in surface water.
Keywords: Sørishavet; alger; biogeokjemi; hydrografi; karbondioksid; marin kjemi; oseanografi

Early spring pack ice algae from the Arctic and Antarctic: how different are they? - McMinn, Andrew; Hegseth, Else N (Backhuys, 2003)
Publication Title: Antarctic biology in a global context : proceedings of the VIIIth SCAR International Biology Symposium
Keywords: Antarktis; alger; biodiversitet; biologi; havis; sjøis

Production and mortality of phytoplankton and sea-ice microalgae in the Southern ocean - Johnsen, Geir; Børsheim, Knut Yngve; Johansen, Torunn (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: Bouvetøya; NARE 2000/01; Sørishavet; alger; fytoplankton; havis; marin biologi; oseanografi; sjøis; zooplankton

Contribution of algal sinking and zooplankton grazing to downward flux in the Lazarev Sea (Southern Ocean) during the onset of phytoplankton bloom: a lagrangian study - Pakhomov, Evgeny A.; Froneman, Pierre W.; Wassmann, Paul; Ratkova, Tatjana; Arashkevich, Elena (Marine Ecology Progress Series, 2002)
ABSTRACT: Hydrography, chlorophyll a, phytoplankton and zooplankton dynamics and the vertical flux of particulate organic carbon (POC) and pigments in the upper 200 m were investigated for 12 consecutive days during a drogue study conducted in the open waters of the ice-edge zone of the Lazarev Sea during the austral summer (December/January) 1994/95. Results of the study indicate that during the experiment, primary production, although variable, increased from ~300 to ~800 mgC m^-2d^-1. This increase could likely be related to development of a shallow pycnocline. Analysis of sediment trap data showed that the vertical carbon flux resulting from sedimentation and grazing activity was greatest in the upper water column (<80 m). The importance of grazers to total POC flux was highest at the beginning and the end of the investigation and accounted for up to 15% of total carbon flux. The contribution of grazers to vertical flux was negligible (<2%) during the intermediate part of the Southern Ocean Drogue study. Lower contribution of grazers to sedimentation of POC at depth can likely be related to community composition of zooplankton. Sedimentation of phytoplankton cells from the upper water column increased during the study. Here, downward POC flux resulting from sedimentation of microphytoplankton was equivalent to 15-75% of the total. Increase in sedimentation of phytoplankton during the study can be related to an increase in the average size of phytoplankton cells. Transport of POC from surface waters to deeper depths resulting from sedimentation or grazing activity was equivalent to <48% of total daily primary production, measured at 50 m, while the same value for phytoplankton flux did not exceed 27% of the total. Zooplankton density was insufficient to exert either a positive (via faecal pellets) or negative (via reducing suspended phytoplankton concentration) effect on particulate carbon sedimentation. This resulted in algal sink being the most important mechanism in downward POC flux during the onset of the phytoplankton bloom period in the Marginal Ice Zone, even in the presence of pelagic tunicates.
Keywords: Sørishavet; alger; biokjemi; marin biologi; oseanografi; phytoplankton; zooplankton

Seaweeds in Cold Seas: Evolution and Carbon Acquisition - Raven, John A.; Johnston, Andrew M.; Kübler, Janet E.; Korb, Rebecca; Mcinroy, Shona G.; Handley, Linda L.; Scrimgeour, Charlie M.; Walker, Diana I.; Beardall, John; Clayton, Margaret M.; Vanderklift, Mathew; Fredriksen, Stein; et al. (Annals of Botany, 2002)
Much evidence suggests that life originated in hydrothermal habitats, and for much of the time since the origin of cyanobacteria (at least 2·5 Ga ago) and of eukaryotic algae (at least 2·1 Ga ago) the average sea surface and land surface temperatures were higher than they are today. However, there have been at least four significant glacial episodes prior to the Pleistocene glaciations. Two of these (approx. 2·1 and 0·7 Ga ago) may have involved a ‘Snowball Earth’ with a very great impact on the algae (sensu lato) of the time (cyanobacteria, Chlorophyta and Rhodophyta) and especially those that were adapted to warm habitats. By contrast, it is possible that heterokont, dinophyte and haptophyte phototrophs only evolved after the Carboniferous–Permian ice age (approx. 250 Ma ago) and so did not encounter low (≤5 °C) sea surface temperatures until the Antarctic cooled some 15 Ma ago. Despite this, many of the dominant macroalgae in cooler seas today are (heterokont) brown algae, and many laminarians cannot reproduce at temperatures above 18–25 °C. By contrast to plants in the aerial environment, photosynthetic structures in water are at essentially the same temperature as the fluid medium. The impact of low temperatures on photosynthesis by marine macrophytes is predicted to favour diffusive CO2 entry rather than a CO2‐concentrating mechanism. Some evidence favours this suggestion, but more data are needed.
Keywords: Sørishavet; alger; biogeografi; botanikk; makroalger; marin biologi